The Features of Educational Development of the Polish Population in the South of Ukraine in 1920-s - Tretiakova, Olha (Pedagogical Discourse, 2015)
In the article on the basis of the archived and other sources the process of development of school education of the Polish national minority in the South of Ukraine in 1920s is examined. The historical places of Polish population’s location are outlined in the South region; specially well-educated public authorities,which are the task of organization of educational work among national minorities are described. Reasons and terms of input of new national politics are defined; normatively-legal acts are analysed on the basis of that the new system of education is created. The process of activity organization of educational establishments for the Polish population is shown. The positive and negative aspects of their activity are determined. As a result of the conducted analysis, we concluded, that the Polish population in two ways and ambiguously behaved to the accrued educational establishments. From one side, networking of national schools with Polish studies had an important value for maintenance of their originality and identity, and from other, wide anti-religious propaganda and planting of communist ideology pushed away the Polish population from the Soviet national schools. Moreover, the badly developed network of Polish schools of the high level, weak material and technical base of studies and absence of skilled Polish teachers, influenced negatively on the quality of studies at the national Polish schools.